Fundamentals of electric power engineering - Mayergoyz, I. D.; McAvoy, Patrick (World Scientific, 2015)
Electric power engineering has always been an integral part of electrical engineering education. Providing a unique alternative to existing books on the market, this compendium provides a concise and rigorous exposition of the main fundamentals of electric power engineering